Positive Charges on the Surface of Thaumatin Are Crucial for the Multi-Point Interaction with the Sweet Receptor - Masuda, Tetsuya; Kigo, Satomi; Mitsumoto, Mayuko; Ohta, Keisuke; Suzuki, Mamoru; Mikami, Bunzo; Kitabatake, Naofumi; Tani, Fumito (Frontiers in Molecular Biosciences, 2018)
Thaumatin, an intensely sweet-tasting protein, elicits sweet taste with a threshold of only 50 nM. Previous studies from our laboratory suggested that the complex model between the T1R2-T1R3 sweet receptor and thaumatin depends critically on the complementarity of electrostatic potentials. In order to further validate this model, we focused on three lysine residues (Lys78, Lys106, and Lys137), which were expected to locate on the interaction sites. Three thaumatin mutants (K78A, K106A, and K137A) were prepared and their threshold values of sweetness were examined. The results showed that the sweetness of K106A was reduced by about three times and those of K78A and K137A were reduced by about five times when compared to wild-type thaumatin. The three-dimensional structures of these mutants were also determined by X-ray crystallographic analyses at atomic resolutions. The overall structures of mutant proteins were similar to that of wild-type but the electrostatic potentials on the mutated sites became more negative. Since these lysine residues are located in 20 to 40 Å apart on the surface of thaumatin, our results are consistent with a large surface of interaction with the sweet receptor, as proposed by the multipoint interaction model between sweet-tasting proteins and sweet receptor named wedge model. The positive charges on the surface of thaumatin play a crucial role in the interaction with the sweet receptor.